2015
DOI: 10.1890/es14-00243.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of carbon isotopes reveals seagrass contribution to fishery food web

Abstract: Citation: Connolly, R. M., and N. J. Waltham. 2015. Spatial analysis of carbon isotopes reveals seagrass contribution to fishery food web. Ecosphere 6(9):148. http://dx.doi.org/10.1890/ES14-00243.1Abstract. Despite the widespread use of carbon stable isotopes to distinguish among potential energy pathways in food webs, their usefulness is limited where potential basal carbon sources are numerous and diverse. We measured carbon isotope values of the major fisheries species, the mostly carnivorous Scylla serrata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 64 publications
3
14
0
Order By: Relevance
“…Overall, there is strong evidence that a light-mediated process and CO 2 limitation drive enrichment of M. pyrifera d 13 C. In the field, we observed that depth, position relative to the kelp bed, and upwelling are strong predictors of d 13 C. Resolving these fine spatial and seasonal drivers of d 13 C variation could give us power similar to that of compoundspecific stable isotope analyses, allowing us to relate d 13 C signatures to microhabitats (Finlay et al 1999;Gillies et al 2011;Connolly and Walthan 2015;Mcmahon et al 2015;McPherson et al 2015). There are many species of young fishes and larval/adult invertebrates that exclusively inhabit the kelp forest canopy; conversely, there are also a substantial subset of species that live their adult lives strictly near or on the seafloor (Ebeling et al 1978;Bernstein and Jung 1979;Coyer 1979;Watanabe 1984;Demartini and Roberts 1990;Hartney 1996).…”
Section: Sourcementioning
confidence: 73%
“…Overall, there is strong evidence that a light-mediated process and CO 2 limitation drive enrichment of M. pyrifera d 13 C. In the field, we observed that depth, position relative to the kelp bed, and upwelling are strong predictors of d 13 C. Resolving these fine spatial and seasonal drivers of d 13 C variation could give us power similar to that of compoundspecific stable isotope analyses, allowing us to relate d 13 C signatures to microhabitats (Finlay et al 1999;Gillies et al 2011;Connolly and Walthan 2015;Mcmahon et al 2015;McPherson et al 2015). There are many species of young fishes and larval/adult invertebrates that exclusively inhabit the kelp forest canopy; conversely, there are also a substantial subset of species that live their adult lives strictly near or on the seafloor (Ebeling et al 1978;Bernstein and Jung 1979;Coyer 1979;Watanabe 1984;Demartini and Roberts 1990;Hartney 1996).…”
Section: Sourcementioning
confidence: 73%
“…Although the proportion of epiphytes contributing to food webs did not change, these findings allude to the notion that greater surface area in seagrass meadows leads to higher availability of epiphytes, which in turn could support a larger community of animals. The importance of epiphytes has been demonstrated in seagrass food webs previously (Bologna and Heck , Moncrieff and Sullivan , Connolly and Waltham ), and herbivorous species are known to prefer leaves covered in epiphytes (Marco‐Méndez et al. ).…”
Section: Discussionmentioning
confidence: 91%
“…An additional hypothesis for the discrepancies between our results and previous studies could also be due to limitations in the ability of stable isotope analyses to distinguish among contributing organic matter sources. As discussed, the number of potential sources of OC in Moreton Bay is large with stable isotope values of 13 C and 15 N of seagrass overlapping with other potential sources, such as C4 vegetation and epiphytic algae (Connolly and Waltham ), which can lead to uncertainties and underetimation of seagrass contributions in mixing model solutions (Fry ). The low taxonomic detail in these previous stable isotope models compared to our use of eDNA could be an additional reason why we found significantly higher autochotonous contributions to seagrass sediment organic matter than those using isotopic modelling.…”
Section: Discussionmentioning
confidence: 99%